Anterior chamber flare after trabeculectomy and after phacoemulsification. Issue 9 (1st September 2000) - Siriwardena, D; Kotecha, A; Minassian, D; Dart, J K G; Khaw, P T
Abstract : AIMS: To evaluate and compare prospectively the anterior chamber inflammatory response after phacoemulsification cataract surgery and after trabeculectomy with peripheral iridectomy. METHODS: Anterior chamber inflammation was measured using the Kowa FM-500 laser flare meter in 131 patients undergoing trabeculectomy and 148 patients undergoing phacoemulsification cataract extraction with intraocular lens implantation. Flare was measured before surgery and on each postoperative visit up to 12 months. RESULTS: Before surgery there was no significant difference in flare readings between the two groups. Following trabeculectomy flare returned to baseline levels 4 weeks after surgery, while following phacoemulsification cataract extraction it remained significantly higher at week 6 (p<0.006) and month 3 (p<0.05). CONCLUSIONS: Anterior chamber inflammation is more prolonged after cataract surgery than after trabeculectomy. This may have implications for the timing of trabeculectomy in relation to cataract surgery.